Method for preparing acetonitrile by catalyzing ethanol ammoxidation through ultramicro high-entropy alloy catalyst

Through the ultramicro PtPdRuAuAg high-entropy alloy/oxide catalytic system, the stability of ethanol ammonia oxidation catalyst in water and ammonia environment was solved, and efficient and sustainable acetonitrile preparation was achieved. The catalyst remained 90% after multiple cycles. The above activities.

CN119285494APending Publication Date: 2025-01-10ZHONGBEI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411409582.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing ethanol ammonia oxidation catalysts have poor stability in the environment of water and ammonia, resulting in the loss of catalyst active components, limiting the industrial application of acetonitrile preparation.

Method used

Using ultramicro PtPdRuAuAg high entropy alloy/oxide heterogeneous catalytic system, the precursors of platinum, palladium, ruthenium, gold and silver are dispersed in volatile low-carbon primary alcohols, and oxide support is added, and the dispersion and slowness are carried out through ultrasonic dispersion. The solvent was evaporated and self-assembled to obtain an oxide-supported PtPdRuAuAg high-entropy alloy catalyst for ethanol ammonia oxidation reaction.

Benefits of technology

The catalyst still maintains more than 90% of its original activity after multiple cycles, significantly improving the cycle stability and achieving an efficient, green and sustainable process for the preparation of acetonitrile by ethanol ammonia oxidation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005077625080000081
    Figure BDA0005077625080000081
  • Figure BDA0005077625080000091
    Figure BDA0005077625080000091
Patent Text Reader

Abstract

The invention relates to a method for preparing acetonitrile by catalyzing ammoxidation of ethanol with an ultramicro high-entropy alloy catalyst. The preparation method of the high-entropy alloy catalyst comprises the following steps: dispersing precursors of platinum, palladium, ruthenium, gold and silver in volatile low-carbon primary alcohol, then adding a proper amount of oxide carrier, carrying out ultrasonic dispersion, placing a suspension of the alcohol in an explosion-proof oven, and carrying out slow solvent evaporation self-assembly to obtain a dry powder sample. And after the powder sample is reduced in a tubular furnace, the oxide-loaded PtPdRuAuAg high-entropy alloy catalyst is obtained. The catalyst is mixed with an ethanol water solution and an ammonia water solution, the mixture is placed in a pressure-resistant reaction kettle to be sealed, oxygen is introduced, a reaction is carried out under stirring, and acetonitrile is prepared through an ammoxidation process. The process is high in catalytic activity and excellent in recycling performance, and after ten times of recycling, the catalytic activity can still be kept 90% of the activity of a fresh catalyst. The catalyst is high in structural stability and excellent in ammonia corrosion resistance, and is an ideal novel ethanol ammoxidation catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing acetonitrile by catalyzing ethanol ammoxidation using an ultrafine high entropy alloy catalyst, and in particular relates to a method for preparing acetonitrile by catalyzing ethanol ammoxidation using an ultrafine oxide-loaded PtPdRuAuAg catalyst. Background Art

[0002] High entropy alloys are new alloys obtained by a specific synthesis of multiple metal elements. Compared with traditional alloys, they have greater configurational entropy. In recent years, researchers have found that they also have special catalytic properties in the field of catalysis. Macroscopic high entropy alloy blocks have high-temperature oxidation resistance, and excellent performance in hardness, ultimate strength and yield strength. When the scale of high entropy alloys is reduced to nanometers or even sub-nanometers, their structural stability, oxidation resistance and corrosion resistance are also excellent.

[0003] The preparation of acetonitrile by ammoxidation of ethanol is a green and sustainable alternative to the traditional synthesis of acetonitrile. Ethanol can be obtained by biomass fermentation, and the one-step ammoxidation process to prepare acetonitrile is simple, with a short process route and good industrial prospects. However, the ammoxidation process also faces some bottlenecks: on the one hand, the ethanol obtained by biological fermentation contains a large amount of water, which requires the catalyst to have good water resistance; on the other hand, there is a strong interaction between ammonia and metals, and the complexation of ammonia will cause the metal components to leach from the solid metal into the reaction solution, resulting in the loss of the active components of the catalyst.

[0004] Therefore, by utilizing the excellent properties of high entropy alloys in structural stability and corrosion resistance, an efficient ethanol ammoxidation catalytic system is developed, which enables the solid catalyst to significantly improve the cyclic stability of the catalyst in an environment containing ammonia and water. It is expected to become a potential industrial catalyst for the future ethanol ammoxidation to acetonitrile process. Summary of the invention

[0005] The significance of the present invention is to apply ultrafine PtPdRuAuAg high entropy alloy catalyst to ethanol ammoxidation to prepare acetonitrile catalyst. The ultrafine PtPdRuAuAg high entropy alloy / oxide multiphase catalytic system is used. After ten cycles of ammoxidation reaction, the reaction activity can still maintain 90% of the original catalytic activity.

[0006] The present invention relates to a method for preparing acetonitrile by catalyzing ethanol ammoxidation with an ultrafine high entropy alloy catalyst, characterized in that: precursors of platinum, palladium, ruthenium, gold and silver are dispersed in a low-carbon primary alcohol that is easy to volatilize, and then an appropriate amount of oxide carrier is added. After ultrasonic dispersion, the alcohol suspension is placed in an explosion-proof oven and undergoes a slow solvent evaporation self-assembly process to obtain a dry powder sample. After the powder sample is reduced in a tube furnace, an oxide-loaded PtPdRuAuAg high entropy alloy catalyst is obtained. The catalyst is mixed with an ethanol aqueous solution and an ammonia aqueous solution, placed in a pressure-resistant reactor, sealed, filled with oxygen and reacted under stirring, and acetonitrile is prepared through an ammoxidation process. The components of the high entropy alloy catalyst are platinum, palladium, ruthenium, gold and silver, the five metal precursors include one of chloride, nitrate and acetate, the amount of each element in the high entropy alloy ranges from 10% to 30%, the high entropy alloy loading is 1% to 5%, and the size of the high entropy alloy nanoparticles is 1.5 to 5nm.

[0007] The carrier oxide is one of aluminum oxide, silicon dioxide, titanium dioxide, zirconium dioxide and cerium dioxide, and the volatile low-carbon primary alcohol includes one or more of methanol, ethanol, propanol and isopropanol; the solvent evaporation temperature is 30-80°C, the tubular furnace reduction temperature is 250-650°C, the reducing atmosphere is a mixture of hydrogen and nitrogen or hydrogen and argon, and the volume ratio of hydrogen is 5%-60%; the volume ratio of ethanol in the ethanol aqueous solution is 1%-10%, the pressure of oxygen is 0.2-1.2MPa, the molar ratio of ammonia to ethanol is 1:1-5:1, and the ammonia oxidation temperature is 40-150°C.

[0008] The method is characterized in that (1) the prepared ultrafine PtPdRuAuAg high entropy alloy catalyst has excellent water resistance and anti-ammonia complexation performance, and can realize ethanol ammoxidation to prepare acetonitrile; (2) the PtPdRuAuAg high entropy alloy / oxide catalyst can be recycled multiple times.

[0009] The present invention has the following advantages: 1. The ultrafine PtPdRuAuAg high entropy alloy catalyst is easy to prepare, has a stable structure and excellent performance; 2. Ethanol ammoxidation is used to prepare acetonitrile, and the process is green and sustainable, and the raw material is renewable energy. DETAILED DESCRIPTION

[0010] In order to further explain the present invention in detail, several specific implementation cases are given below, but the present invention is not limited to these embodiments.

[0011] Example 1

[0012] Equimolar amounts of chloroplatinic acid, chloropalladic acid, ruthenium trichloride, chloroauric acid and silver nitrate were dissolved in ethanol, and CeO2 carrier was added to the solution under stirring. After 30 minutes of ultrasonic treatment, the suspension was placed in an explosion-proof oven at 30°C for solvent evaporation self-assembly process to obtain a dry powder sample. The powder sample was placed in a tube furnace at 500°C in a hydrogen-argon mixed gas (hydrogen volume ratio 10%) atmosphere for reduction to obtain a ceria-loaded PtPdRuAuAg high entropy alloy catalyst (PtPdRuAuAg / CeO2). The loading amount of the high entropy alloy was 2wt%.

[0013] The prepared PtPdRuAuAg / CeO2 catalyst was added to an intermittent reactor, the volume ratio of ethanol in the ethanol aqueous solution was 1%, the molar ratio of ethanol to high entropy alloy was 100:1, the pressure of oxygen was 1.2 MPa, the molar ratio of ammonia to ethanol was 5:1, and the ammonia oxidation reaction was stirred at 100°C for 10 hours. After the reaction, the reactor was placed in an ice water bath for cooling. After the catalyst was centrifuged, the supernatant was taken for analysis, and the yield of acetonitrile was 94 mol%. The reacted catalyst was washed and dried and used for the second cycle reaction. After ten times, the yield of acetonitrile was 84.6 mol%.

[0014] Example 2

[0015] Equimolar amounts of chloroplatinic acid, palladium nitrate, ruthenium nitrate, chloroauric acid and silver nitrate were dissolved in ethanol, and an Al2O3 carrier was added to the solution under stirring. After ultrasonic treatment for 30 minutes, the suspension was placed in an explosion-proof oven at 40°C for solvent evaporation and self-assembly to obtain a dry powder sample. The powder sample was placed in a tube furnace at 400°C in a hydrogen-argon mixed gas (hydrogen volume ratio 20%) atmosphere for reduction to obtain an alumina-supported PtPdRuAuAg high entropy alloy catalyst (PtPdRuAuAg / Al2O3). The loading amount of the high entropy alloy was 5wt%.

[0016] The prepared PtPdRuAuAg / Al2O3 catalyst was added to an intermittent reactor, the volume ratio of ethanol in the ethanol aqueous solution was 5%, the molar ratio of ethanol to high entropy alloy was 200:1, the pressure of oxygen was 0.5 MPa, the molar ratio of ammonia to ethanol was 2:1, and the ammonia oxidation reaction was stirred at 70°C for 10 hours. After the reaction, the reactor was placed in an ice water bath for cooling. After the catalyst was centrifuged, the supernatant was taken for analysis, and the yield of acetonitrile was 82.7 mol%. The reacted catalyst was washed and dried and used for the second cycle reaction. After ten times, the yield of acetonitrile was 74.6 mol%.

[0017] Example 3

[0018] Equimolar amounts of chloroplatinic acid, chloropalladic acid, ruthenium trichloride, chloroauric acid and silver nitrate were dissolved in a mixed alcohol solution of methanol and isopropanol, and CeO2 carrier was added to the solution under stirring. After 30 minutes of ultrasonic treatment, the suspension was placed in an explosion-proof oven at 30°C for solvent evaporation self-assembly process to obtain a dry powder sample. The powder sample was placed in a tube furnace at 500°C in a hydrogen-argon mixed gas (hydrogen volume ratio 10%) atmosphere for reduction to obtain a ceria-loaded PtPdRuAuAg high entropy alloy catalyst (PtPdRuAuAg / CeO2). The loading amount of the high entropy alloy was 2wt%.

[0019] The prepared PtPdRuAuAg / CeO2 catalyst was added to an intermittent reactor, the volume ratio of ethanol in the ethanol aqueous solution was 1%, the molar ratio of ethanol to high entropy alloy was 100:1, the pressure of oxygen was 1.2 MPa, the molar ratio of ammonia to ethanol was 5:1, and the ammonia oxidation reaction was stirred at 100°C for 10 hours. After the reaction, the reactor was placed in an ice water bath for cooling. After the catalyst was centrifuged, the supernatant was taken for analysis, and the yield of acetonitrile was 93 mol%. The reacted catalyst was washed and dried and used for the second cycle reaction. After ten times, the yield of acetonitrile was 82 mol%.

[0020] Example 4

[0021] Equimolar amounts of chloroplatinic acid, chloropalladic acid, ruthenium trichloride, chloroauric acid and silver nitrate were dissolved in ethanol, and CeO2 carrier was added to the solution under stirring. After 30 minutes of ultrasonic treatment, the suspension was placed in an explosion-proof oven at 30°C for solvent evaporation self-assembly process to obtain a dry powder sample. The powder sample was placed in a tube furnace at 500°C in a hydrogen-argon mixed gas (hydrogen volume ratio 10%) atmosphere for reduction to obtain a ceria-loaded PtPdRuAuAg high entropy alloy catalyst (PtPdRuAuAg / CeO2). The loading amount of the high entropy alloy was 2wt%.

[0022] The prepared PtPdRuAuAg / CeO2 catalyst was added to an intermittent reactor, the volume ratio of ethanol in the ethanol aqueous solution was 1%, the molar ratio of ethanol to high entropy alloy was 100:1, the pressure of oxygen was 1.2 MPa, the molar ratio of ammonia to ethanol was 5:1, and the ammonia oxidation reaction was stirred at 100°C for 10 hours. After the reaction, the reactor was placed in an ice water bath for cooling. After the catalyst was centrifuged, the supernatant was taken for analysis, and the yield of acetonitrile was 90.2 mol%. The reacted catalyst was washed and dried and used for the second cycle reaction. After ten times, the yield of acetonitrile was 80 mol%.

[0023] Example 5

[0024] Equimolar amounts of chloroplatinic acid, palladium nitrate, ruthenium trichloride, chloroauric acid and silver nitrate were dissolved in ethanol, and CeO2 carrier was added to the solution under stirring. After 30 minutes of ultrasonic treatment, the suspension was placed in an explosion-proof oven at 30°C for solvent evaporation self-assembly process to obtain a dry powder sample. The powder sample was placed in a tube furnace at 500°C in a hydrogen-argon mixed gas (hydrogen volume ratio 10%) atmosphere for reduction to obtain a ceria-supported PtPdRuAuAg high entropy alloy catalyst (PtPdRuAuAg / CeO2). The loading amount of the high entropy alloy was 2wt%.

[0025] The prepared PtPdRuAuAg / CeO2 catalyst was added to an intermittent reactor, the volume ratio of ethanol in the ethanol aqueous solution was 1%, the molar ratio of ethanol to high entropy alloy was 100:1, the pressure of oxygen was 1.2 MPa, the molar ratio of ammonia to ethanol was 5:1, and the ammonia oxidation reaction was stirred at 100°C for 10 hours. After the reaction, the reactor was placed in an ice water bath for cooling. After the catalyst was centrifuged, the supernatant was taken for analysis, and the yield of acetonitrile was 87.3 mol%. The reacted catalyst was washed and dried and used for the second cycle reaction. After ten times, the yield of acetonitrile was 79.5 mol%.

[0026] Example 6

[0027] Equimolar amounts of chloroplatinic acid, chloropalladic acid, ruthenium nitrate, chloroauric acid and silver nitrate were dissolved in ethanol, and CeO2 carrier was added to the solution under stirring. After ultrasonic treatment for 30 minutes, the suspension was placed in an explosion-proof oven at 30°C for solvent evaporation self-assembly process to obtain a dry powder sample. The powder sample was placed in a tube furnace at 500°C in a hydrogen-argon mixed gas (hydrogen volume ratio 10%) atmosphere for reduction to obtain a ceria-supported PtPdRuAuAg high entropy alloy catalyst (PtPdRuAuAg / CeO2). The loading amount of the high entropy alloy was 2wt%.

[0028] The prepared PtPdRuAuAg / CeO2 catalyst was added to an intermittent reactor, the volume ratio of ethanol in the ethanol aqueous solution was 1%, the molar ratio of ethanol to high entropy alloy was 100:1, the pressure of oxygen was 1.2 MPa, the molar ratio of ammonia to ethanol was 5:1, and the ammonia oxidation reaction was stirred at 100°C for 10 hours. After the reaction, the reactor was placed in an ice water bath for cooling. After the catalyst was centrifuged, the supernatant was taken for analysis, and the yield of acetonitrile was 92.5 mol%. The reacted catalyst was washed and dried and used for the second cycle reaction. After ten times, the yield of acetonitrile was 81.8 mol%.

[0029] Example 7

[0030] Equimolar amounts of chloroplatinic acid, chloropalladic acid, ruthenium trichloride, chloroauric acid and silver nitrate were dissolved in methanol, and CeO2 carrier was added to the solution under stirring. After 30 minutes of ultrasonic treatment, the suspension was placed in an explosion-proof oven at 30°C for solvent evaporation self-assembly process to obtain a dry powder sample. The powder sample was placed in a tube furnace at 500°C in a hydrogen-argon mixed gas (hydrogen volume ratio 10%) atmosphere for reduction to obtain a ceria-loaded PtPdRuAuAg high entropy alloy catalyst (PtPdRuAuAg / CeO2). The loading amount of the high entropy alloy was 2wt%.

[0031] The prepared PtPdRuAuAg / CeO2 catalyst was added to an intermittent reactor, the volume ratio of ethanol in the ethanol aqueous solution was 1%, the molar ratio of ethanol to high entropy alloy was 100:1, the pressure of oxygen was 1.2 MPa, the molar ratio of ammonia to ethanol was 5:1, and the ammonia oxidation reaction was stirred at 100°C for 10 hours. After the reaction, the reactor was placed in an ice water bath for cooling. After the catalyst was centrifuged, the supernatant was taken for analysis, and the yield of acetonitrile was 93.4 mol%. The reacted catalyst was washed and dried and used for the second cycle reaction. After ten times, the yield of acetonitrile was 84 mol%.

[0032] Example 8

[0033] Equimolar amounts of chloroplatinic acid, chloropalladic acid, ruthenium trichloride, chloroauric acid and silver nitrate were dissolved in ethanol, and a ZrO2 carrier was added to the solution under stirring. After 30 minutes of ultrasonic treatment, the suspension was placed in an explosion-proof oven at 30°C for solvent evaporation and self-assembly to obtain a dry powder sample. The powder sample was placed in a tube furnace at 500°C in a hydrogen-argon mixed gas (hydrogen volume ratio 10%) atmosphere for reduction to obtain a ceria-supported PtPdRuAuAg high entropy alloy catalyst (PtPdRuAuAg / ZrO2). The loading amount of the high entropy alloy was 2wt%.

[0034] The prepared PtPdRuAuAg / ZrO2 catalyst was added to an intermittent reactor, the volume ratio of ethanol in the ethanol aqueous solution was 1%, the molar ratio of ethanol to high entropy alloy was 100:1, the pressure of oxygen was 1.2 MPa, the molar ratio of ammonia to ethanol was 5:1, and the ammonia oxidation reaction was stirred at 100°C for 10 hours. After the reaction, the reactor was placed in an ice water bath for cooling. After the catalyst was centrifuged, the supernatant was taken for analysis, and the yield of acetonitrile was 82.7 mol%. The reacted catalyst was washed and dried and used for the second cycle reaction. After ten times, the yield of acetonitrile was 74.6 mol%.

[0035] Example 9

[0036] Equimolar amounts of chloroplatinic acid, chloropalladic acid, ruthenium trichloride, chloroauric acid and silver nitrate were dissolved in ethanol, and a TiO2 carrier was added to the solution under stirring. After 30 minutes of ultrasonic treatment, the suspension was placed in an explosion-proof oven at 30°C for solvent evaporation and self-assembly to obtain a dry powder sample. The powder sample was placed in a tube furnace at 500°C in a hydrogen-argon mixed gas (hydrogen volume ratio 10%) atmosphere for reduction to obtain a ceria-supported PtPdRuAuAg high entropy alloy catalyst (PtPdRuAuAg / TiO2). The loading amount of the high entropy alloy was 2wt%.

[0037] The prepared PtPdRuAuAg / TiO2 catalyst was added to an intermittent reactor, the volume ratio of ethanol in the ethanol aqueous solution was 1%, the molar ratio of ethanol to high entropy alloy was 100:1, the pressure of oxygen was 1.2 MPa, the molar ratio of ammonia to ethanol was 5:1, and the ammonia oxidation reaction was stirred at 100°C for 10 hours. After the reaction, the reactor was placed in an ice water bath for cooling. After the catalyst was centrifuged, the supernatant was taken for analysis, and the yield of acetonitrile was 89 mol%. The reacted catalyst was washed and dried and used for the second cycle reaction. After ten times, the yield of acetonitrile was 73.6 mol%.

[0038] Example 10

[0039] Equimolar amounts of chloroplatinic acid, chloropalladic acid, ruthenium trichloride, chloroauric acid and silver nitrate were dissolved in ethanol, and CeO2 carrier was added to the solution under stirring. After ultrasonic treatment for 30 minutes, the suspension was placed in an explosion-proof oven at 80°C for solvent evaporation self-assembly process to obtain a dry powder sample. The powder sample was placed in a tube furnace at 500°C in a hydrogen-argon mixed gas (hydrogen volume ratio 10%) atmosphere for reduction to obtain a ceria-supported PtPdRuAuAg high entropy alloy catalyst (PtPdRuAuAg / CeO2). The loading amount of the high entropy alloy was 2wt%.

[0040] The prepared PtPdRuAuAg / CeO2 catalyst was added to an intermittent reactor, the volume ratio of ethanol in the ethanol aqueous solution was 1%, the molar ratio of ethanol to high entropy alloy was 100:1, the pressure of oxygen was 1.2 MPa, the molar ratio of ammonia to ethanol was 5:1, and the ammonia oxidation reaction was stirred at 100°C for 10 hours. After the reaction, the reactor was placed in an ice water bath for cooling. After the catalyst was centrifuged, the supernatant was taken for analysis, and the yield of acetonitrile was 85.8 mol%. The reacted catalyst was washed and dried and used for the second cycle reaction. After ten times, the yield of acetonitrile was 77.2 mol%.

[0041] Embodiment 11

[0042] Equimolar amounts of chloroplatinic acid, chloropalladic acid, ruthenium trichloride, chloroauric acid and silver nitrate were dissolved in ethanol, and CeO2 carrier was added to the solution under stirring. After 30 minutes of ultrasonic treatment, the suspension was placed in an explosion-proof oven at 30°C for solvent evaporation self-assembly process to obtain a dry powder sample. The powder sample was placed in a tube furnace at 500°C in a hydrogen-argon mixed gas (hydrogen volume ratio 10%) atmosphere for reduction to obtain a ceria-supported PtPdRuAuAg high entropy alloy catalyst (PtPdRuAuAg / CeO2). The loading amount of the high entropy alloy was 5wt%.

[0043] The prepared PtPdRuAuAg / CeO2 catalyst was added to an intermittent reactor, the volume ratio of ethanol in the ethanol aqueous solution was 1%, the molar ratio of ethanol to high entropy alloy was 100:1, the pressure of oxygen was 1.2 MPa, the molar ratio of ammonia to ethanol was 5:1, and the ammonia oxidation reaction was stirred at 100°C for 10 hours. After the reaction, the reactor was placed in an ice water bath for cooling. After the catalyst was centrifuged, the supernatant was taken for analysis, and the yield of acetonitrile was 86.9 mol%. The reacted catalyst was washed and dried and used for the second cycle reaction. After ten times, the yield of acetonitrile was 78.6 mol%.

[0044] Example 12

[0045] Equimolar amounts of chloroplatinic acid, chloropalladic acid, ruthenium trichloride, chloroauric acid and silver nitrate were dissolved in ethanol, and CeO2 carrier was added to the solution under stirring. After 30 minutes of ultrasonic treatment, the suspension was placed in an explosion-proof oven at 30°C for solvent evaporation self-assembly process to obtain a dry powder sample. The powder sample was placed in a tube furnace at 500°C in a hydrogen-argon mixed gas (hydrogen volume ratio 10%) atmosphere for reduction to obtain a ceria-loaded PtPdRuAuAg high entropy alloy catalyst (PtPdRuAuAg / CeO2). The loading amount of the high entropy alloy was 1wt%.

[0046] The prepared PtPdRuAuAg / CeO2 catalyst was added to an intermittent reactor, the volume ratio of ethanol in the ethanol aqueous solution was 1%, the molar ratio of ethanol to high entropy alloy was 100:1, the pressure of oxygen was 1.2 MPa, the molar ratio of ammonia to ethanol was 5:1, and the ammonia oxidation reaction was stirred at 100°C for 10 hours. After the reaction, the reactor was placed in an ice water bath for cooling. After the catalyst was centrifuged, the supernatant was taken for analysis, and the yield of acetonitrile was 90.4 mol%. The reacted catalyst was washed and dried and used for the second cycle reaction. After ten times, the yield of acetonitrile was 81.3 mol%.

[0047] Embodiment 13

[0048] Equimolar amounts of chloroplatinic acid, chloropalladic acid, ruthenium trichloride, chloroauric acid and silver nitrate were dissolved in ethanol, and CeO2 carrier was added to the solution under stirring. After ultrasonic treatment for 30 minutes, the suspension was placed in an explosion-proof oven at 30°C for solvent evaporation self-assembly process to obtain a dry powder sample. The powder sample was placed in a tube furnace at 250°C in a hydrogen-argon mixed gas (hydrogen volume ratio 10%) atmosphere for reduction to obtain a ceria-loaded PtPdRuAuAg high entropy alloy catalyst (PtPdRuAuAg / CeO2). The loading amount of the high entropy alloy was 2wt%.

[0049] The prepared PtPdRuAuAg / CeO2 catalyst was added to an intermittent reactor, the volume ratio of ethanol in the ethanol aqueous solution was 1%, the molar ratio of ethanol to high entropy alloy was 100:1, the pressure of oxygen was 0.2 MPa, the molar ratio of ammonia to ethanol was 5:1, and the ammonia oxidation reaction was stirred at 100°C for 10 hours. After the reaction, the reactor was placed in an ice water bath for cooling. After the catalyst was centrifuged, the supernatant was taken for analysis, and the yield of acetonitrile was 81.5 mol%. The reacted catalyst was washed and dried and used for the second cycle reaction. After ten times, the yield of acetonitrile was 68.1 mol%.

[0050] Embodiment 14

[0051] Equimolar amounts of chloroplatinic acid, chloropalladic acid, ruthenium trichloride, chloroauric acid and silver nitrate were dissolved in ethanol, and CeO2 carrier was added to the solution under stirring. After 30 minutes of ultrasonic treatment, the suspension was placed in an explosion-proof oven at 30°C for solvent evaporation self-assembly process to obtain a dry powder sample. The powder sample was placed in a tube furnace at 650°C in a hydrogen-argon mixed gas (hydrogen volume ratio 10%) atmosphere for reduction to obtain a ceria-loaded PtPdRuAuAg high entropy alloy catalyst (PtPdRuAuAg / CeO2). The loading amount of the high entropy alloy was 2wt%.

[0052] The prepared PtPdRuAuAg / CeO2 catalyst was added to an intermittent reactor, the volume ratio of ethanol in the ethanol aqueous solution was 1%, the molar ratio of ethanol to high entropy alloy was 100:1, the pressure of oxygen was 1.2 MPa, the molar ratio of ammonia to ethanol was 5:1, and the ammonia oxidation reaction was stirred at 100°C for 10 hours. After the reaction, the reactor was placed in an ice water bath for cooling. After the catalyst was centrifuged, the supernatant was taken for analysis, and the yield of acetonitrile was 84.9 mol%. The reacted catalyst was washed and dried and used for the second cycle reaction. After ten times, the yield of acetonitrile was 74.6 mol%.

[0053] Embodiment 15

[0054] Equimolar amounts of chloroplatinic acid, palladium acetate, ruthenium trichloride, chloroauric acid and silver nitrate were dissolved in ethanol, and CeO2 carrier was added to the solution under stirring. After ultrasonic treatment for 30 minutes, the suspension was placed in an explosion-proof oven at 30°C for solvent evaporation self-assembly process to obtain a dry powder sample. The powder sample was placed in a tube furnace at 500°C in a hydrogen-argon mixed gas (hydrogen volume ratio 10%) atmosphere for reduction to obtain a ceria-loaded PtPdRuAuAg high entropy alloy catalyst (PtPdRuAuAg / CeO2). The loading amount of the high entropy alloy was 2wt%.

[0055] The prepared PtPdRuAuAg / CeO2 catalyst was added to an intermittent reactor, the volume ratio of ethanol in the ethanol aqueous solution was 1%, the molar ratio of ethanol to high entropy alloy was 100:1, the pressure of oxygen was 1.2 MPa, the molar ratio of ammonia to ethanol was 5:1, and the ammonia oxidation reaction was stirred at 100°C for 10 hours. After the reaction, the reactor was placed in an ice water bath for cooling. After the catalyst was centrifuged, the supernatant was taken for analysis, and the yield of acetonitrile was 87.4 mol%. The reacted catalyst was washed and dried and used for the second cycle reaction. After ten times, the yield of acetonitrile was 84.6 mol%.

[0056] Example 16

[0057] Equimolar amounts of chloroplatinic acid, chloropalladic acid, ruthenium trichloride, chloroauric acid and silver nitrate were dissolved in ethanol, and CeO2 carrier was added to the solution under stirring. After 30 minutes of ultrasonic treatment, the suspension was placed in an explosion-proof oven at 30°C for solvent evaporation self-assembly process to obtain a dry powder sample. The powder sample was placed in a tube furnace at 500°C in a hydrogen-argon mixed gas (hydrogen volume ratio 5%) atmosphere for reduction to obtain a ceria-supported PtPdRuAuAg high entropy alloy catalyst (PtPdRuAuAg / CeO2). The loading amount of the high entropy alloy was 2wt%.

[0058] The prepared PtPdRuAuAg / CeO2 catalyst was added to an intermittent reactor, the volume ratio of ethanol in the ethanol aqueous solution was 1%, the molar ratio of ethanol to high entropy alloy was 100:1, the pressure of oxygen was 1.2 MPa, the molar ratio of ammonia to ethanol was 5:1, and the ammonia oxidation reaction was stirred at 100°C for 10 hours. After the reaction, the reactor was placed in an ice water bath for cooling. After the catalyst was centrifuged, the supernatant was taken for analysis, and the yield of acetonitrile was 89.2 mol%. The reacted catalyst was washed and dried and used for the second cycle reaction. After ten times, the yield of acetonitrile was 81.4 mol%.

[0059] Embodiment 17

[0060] Equimolar amounts of chloroplatinic acid, chloropalladic acid, ruthenium trichloride, chloroauric acid and silver nitrate were dissolved in ethanol, and CeO2 carrier was added to the solution under stirring. After 30 minutes of ultrasonic treatment, the suspension was placed in an explosion-proof oven at 30°C for solvent evaporation self-assembly process to obtain a dry powder sample. The powder sample was placed in a tube furnace at 500°C in a hydrogen-argon mixed gas (hydrogen volume ratio 60%) atmosphere for reduction to obtain a ceria-supported PtPdRuAuAg high entropy alloy catalyst (PtPdRuAuAg / CeO2). The loading amount of the high entropy alloy was 2wt%.

[0061] The prepared PtPdRuAuAg / CeO2 catalyst was added to an intermittent reactor, the volume ratio of ethanol in the ethanol aqueous solution was 1%, the molar ratio of ethanol to high entropy alloy was 100:1, the pressure of oxygen was 1.2 MPa, the molar ratio of ammonia to ethanol was 5:1, and the ammonia oxidation reaction was stirred at 100°C for 10 hours. After the reaction, the reactor was placed in an ice water bath for cooling. After the catalyst was centrifuged, the supernatant was taken for analysis, and the yield of acetonitrile was 93.7 mol%. The reacted catalyst was washed and dried and used for the second cycle reaction. After ten times, the yield of acetonitrile was 84.5 mol%.

[0062] Comparative Example 1

[0063] Dissolve chloroplatinic acid in ethanol, add CeO2 carrier to the solution under stirring, and after ultrasonication for 30 minutes, place the suspension in an explosion-proof oven at 30°C for solvent evaporation self-assembly process to obtain a dry powder sample. The powder sample is placed in a tube furnace at 500°C in a hydrogen-argon mixed gas (hydrogen volume ratio 10%) atmosphere for reduction to obtain a cerium dioxide-supported Pt catalyst (Pt / CeO2). The Pt loading is 2wt%.

[0064] The prepared Pt / CeO2 catalyst was added to an intermittent reactor, the volume ratio of ethanol in the ethanol aqueous solution was 1%, the molar ratio of ethanol to high entropy alloy was 100:1, the pressure of oxygen was 1.2 MPa, the molar ratio of ammonia to ethanol was 5:1, and the ammonia oxidation reaction was stirred at 100°C for 10 hours. After the reaction, the reactor was placed in an ice water bath for cooling. After the catalyst was centrifuged, the supernatant was taken for analysis, and the yield of acetonitrile was 40.2 mol%. The reacted catalyst was washed and dried and used for the second cycle reaction. After ten times, the yield of acetonitrile was 21.5 mol%.

[0065] Comparative Example 2

[0066] Chloropaldic acid was dissolved in ethanol, and CeO2 carrier was added to the solution under stirring. After ultrasonic treatment for 30 minutes, the suspension was placed in an explosion-proof oven at 30°C for solvent evaporation and self-assembly process to obtain a dry powder sample. The powder sample was placed in a tube furnace at 500°C in a hydrogen-argon mixed gas (hydrogen volume ratio 10%) atmosphere for reduction to obtain a ceria-supported Pd catalyst (Pd / CeO2). The Pd loading was 2wt%.

[0067] The prepared Pd / CeO2 catalyst was added to an intermittent reactor, the volume ratio of ethanol in the ethanol aqueous solution was 1%, the molar ratio of ethanol to high entropy alloy was 100:1, the pressure of oxygen was 1.2 MPa, the molar ratio of ammonia to ethanol was 5:1, and the ammonia oxidation reaction was stirred at 100°C for 10 hours. After the reaction, the reactor was placed in an ice water bath for cooling. After the catalyst was centrifuged, the supernatant was taken for analysis, and the yield of acetonitrile was 43.8 mol%. The reacted catalyst was washed and dried and used for the second cycle reaction. After ten times, the yield of acetonitrile was 25.2 mol%.

[0068] Comparative Example 3

[0069] Ruthenium trichloride was dissolved in ethanol, and CeO2 carrier was added to the solution under stirring. After ultrasonic treatment for 30 minutes, the suspension was placed in an explosion-proof oven at 30°C for solvent evaporation self-assembly process to obtain a dry powder sample. The powder sample was placed in a tube furnace at 500°C in a hydrogen-argon mixed gas (hydrogen volume ratio 10%) atmosphere for reduction to obtain a ceria-supported Ru catalyst (Ru / CeO2). The Ru loading was 2wt%.

[0070] The prepared Ru / CeO2 catalyst was added to an intermittent reactor, the volume ratio of ethanol in the ethanol aqueous solution was 1%, the molar ratio of ethanol to high entropy alloy was 100:1, the pressure of oxygen was 1.2 MPa, the molar ratio of ammonia to ethanol was 5:1, and the ammonia oxidation reaction was stirred at 100°C for 10 hours. After the reaction, the reactor was placed in an ice water bath for cooling. After the catalyst was centrifuged, the supernatant was taken for analysis, and the yield of acetonitrile was 52.8 mol%. The reacted catalyst was washed and dried and used for the second cycle reaction. After ten times, the yield of acetonitrile was 34.2 mol%.

[0071] Table 1 Performance of catalysts prepared in Examples 1 to 13 and Comparative Examples 1 to 3

[0072]

[0073]

[0074] As can be seen from Table 1, the yield of acetonitrile for the fresh catalyst prepared in Examples 1 to 13 of the present invention can reach more than 81%, and the yield of acetonitrile for the catalyst after ten cycles of reaction can still reach more than 68%, indicating that the catalyst has excellent ammoxidation performance and high catalyst structural stability. By comparing the evaluation results of Comparative Examples 1 to 3 with the results of Examples 1 to 13, it can be seen that the five-element high entropy alloy catalyst has more excellent catalytic performance and better cycle stability, and its excellent catalytic activity and stability are mainly derived from the electronic structure characteristics of the high entropy alloy and the high entropy increase effect and hysteresis diffusion effect.

Claims

1. A method for preparing acetonitrile by catalyzing the ammoxidation of ethanol using an ultrafine high entropy alloy catalyst, characterized in that: Precursors of platinum, palladium, ruthenium, gold and silver are dispersed in a low-carbon primary alcohol that is easy to volatilize, and then an appropriate amount of oxide carrier is added. After ultrasonic dispersion, the alcohol suspension is placed in an explosion-proof oven and undergoes a slow solvent evaporation self-assembly process to obtain a dry powder sample. After the powder sample is reduced in a tube furnace, an oxide-supported PtPdRuAuAg high-entropy alloy catalyst is obtained. The catalyst is mixed with an ethanol aqueous solution and an ammonia aqueous solution, placed in a pressure-resistant reactor, sealed, filled with oxygen and reacted under stirring, and acetonitrile is prepared through an ammoxidation process.

2. The method according to claim 1, characterized in that: The components of the high entropy alloy catalyst are platinum, palladium, ruthenium, gold and silver. The five metal precursors include one of chloride, nitrate and acetate. The amount of each element in the high entropy alloy ranges from 10% to 30%, the high entropy alloy loading is 1% to 5%, and the size of the high entropy alloy nanoparticles is 1.5 to 5 nm.

3. The method according to claim 1, characterized in that: The carrier oxide is one of aluminum oxide, silicon dioxide, titanium dioxide, zirconium dioxide and cerium dioxide, and the volatile low-carbon primary alcohol includes one or more of methanol, ethanol, propanol and isopropanol.

4. The method according to claim 1, characterized in that: The solvent evaporation temperature is 30-80°C, the tubular furnace reduction temperature is 250-650°C, the reducing atmosphere is a mixture of hydrogen and nitrogen or hydrogen and argon, and the volume ratio of hydrogen is 5%-60%.

5. The method according to claim 1, characterized in that: The volume ratio of ethanol in the ethanol aqueous solution is 1% to 10%, the pressure of oxygen is 0.2 to 1.2 MPa, the molar ratio of ammonia to ethanol is 1:1 to 5:1, and the ammonia oxidation temperature is 40 to 150°C.